Land development in the light of the objectives of Shariah (Maqasid) - Mohamad, Nor Asiah (Malaysian Current Law Journal, 2015)
The main objectives of the Shariah is to provide a basis to govern all aspects of Muslim life. The ultimate goal of Shariah is to be a bleassing for mankind. This is the primary purpose for which the Prophet Muhammad (SAW) was sent to this world. It is universally accepted that the primary purpose of development is to promote human well-being. In this respect, Islam identifies some of the recognised components for sustainbale well-being as among others; the security of life, property and honour, individual freedom, moral as well as material education, marriage, family management and social solidarity, minimisation of corruption, breach of trust, and fraud. It is argued that the emphasis on some elements for human sustainable well-being lacks on spiritual foundation. It is also argued that it may not be possible to promote sustainable development without ensuring adequate satisfaction of all human well-being requirement. In this article, the objectives of Shariah (maqasid shariah) are addressed as the determining fators, which, if properly understood and translated into practice, would become an important tool in realising sustainbale development agenda.